Accurate 5 Accounting Application Competency Improvement for High School Students - Rin Rin Meilani Salim; Hanes Hanes; Paulus Paulus (Dinamisia : Jurnal Pengabdian Kepada Masyarakat, 2023)
SMA Swasta Panglima Polem is one of the high schools located in Labuhan Batu districts. This school has been accredited A and has 2 (two) majors, namely Natural Sciences (IA) and Social Sciences (IS). The problem that occurs is that there is a gap between accounting subjects and their application in the world of work today. This is not in line with the development of the accounting sector which has utilized Information and Communication Technology (ICT). Students need the ability and knowledge in using accounting applications. In addition, students also need to be instilled with a thorough attitude and the ability to solve problems so that every job can be completed properly and correctly. Students' understanding of accounting is only obtained through theory and practice from books, so students do not have an idea of ​​how the flow of the accounting system runs in a company. Accurate 5 training is given to students for 3 days starting with the opening of the training, introduction of applications, conducting financial transactions, viewing and analyzing financial reports, to conducting post-tests to students. The training went good and showed good results. This is shown by the enthusiasm of the students, the appreciation of the principal, and the results of the training which show an increase in students' understanding of accounting applications, especially Accurate 5.